2019
DOI: 10.1021/acs.jmedchem.9b00939
|View full text |Cite
|
Sign up to set email alerts
|

Novel Brain-Tumor-Inhibiting Copper(II) Compound Based on a Human Serum Albumin (HSA)-Cell Penetrating Peptide Conjugate

Abstract: It is a great challenge to design drugs that penetrate the blood–brain barrier to inhibit brain tumor growth by acting against multiple targets and also improve their delivery efficacy and targeting ability to cancer cells. To overcome the above problems, we designed a multitarget metal agent for treating brain tumors based on an human serum albumin (HSA)-cell penetrating peptide conjugate. Thus, we rationally screened copper (Cu) and 2-acetyl-3-ethylpyrazine thiosemicarbazones to synthesize six compounds, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…31,32 In addition, as copper ions have been involved in cell signaling pathways, the corresponding metal complexes could be able to influence different cell death mechanisms. 30,33 To date, copper complexes were reported inducing various types of nonapoptotic cell death, such as paraptosis, 34 autophagy, 35 or necrosis. 36 Until now, no examples of copper complexes that induce autophagy-dependent apoptosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In addition, as copper ions have been involved in cell signaling pathways, the corresponding metal complexes could be able to influence different cell death mechanisms. 30,33 To date, copper complexes were reported inducing various types of nonapoptotic cell death, such as paraptosis, 34 autophagy, 35 or necrosis. 36 Until now, no examples of copper complexes that induce autophagy-dependent apoptosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As a trace element, copper plays a critical role in cancer development and tumorigenesis. Interestingly, tumor tissue was found with an increased amount of copper in comparison to healthy tissue, providing potentially a naturally occurring cancer tumor-targeting effect. , In addition, as copper ions have been involved in cell signaling pathways, the corresponding metal complexes could be able to influence different cell death mechanisms. , To date, copper complexes were reported inducing various types of nonapoptotic cell death, such as paraptosis, autophagy, or necrosis . Until now, no examples of copper complexes that induce autophagy-dependent apoptosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the terminal H at N-4 of thiosemicarbazone modified with alkyl groups can improve its lipophilicity along with its anticancer activity. [23][24][25][26][27] We thus synthesised a series of novel Pt(II) complexes with 2-thiazolecarboxaldehyde thiosemicarbazones as ligands and investigated crucial structural-activity relationships that enable thiosemicarbazones of this category to be effective against cisplatin-resistant cancer cells. For the purpose of this study, we conducted the following experiments: (1) we synthesised a series of Pt(II) 2-thiazolecarboxaldehyde thiosemicarbazone complexes and explored their structure-activity relationships in cisplatin-resistant cancer cells; (2) we identified the therapeutic efficacy of Pt complexes in cisplatin-resistant A549cisR tumour xenografts; (3) we investigated the effectiveness of Pt complexes in targeting cisplatinresistant cancer cells and their potential mechanism of action; and (4) we confirmed and illuminated in detail the mechanism of Pt complexes in overcoming cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Excitingly, albumin has become one of the most promising carriers for overcoming the challenges mentioned above . Recently, albumin NPs have been designed to enhance the therapeutic efficiency and targeting ability in vivo . Albumin conjugates have been designed to enhance the targeting ability of metal agents for photodynamic therapy. HSA–metal agent complex delivery systems have been constructed to improve their targeting ability and decrease their side effects in vivo . …”
Section: Introductionmentioning
confidence: 99%